Public Administration in Germany
XXIV, 416 p. 7 illus.
Keywords: This open access book presents a topical, comprehensive and differentiated analysis of Germany’s public administration and reforms. It provides an overview on key elements of German public administration at the federal, Länder and local levels of government as well as on current reform activities of the public sector. It examines the key institutional features of German public administration; the changing relationships between public administration, society and the private sector; the administrative reforms at different levels of the federal system and numerous sectors; and new challenges and modernization approaches like digitalization, Open Government and Better Regulation. Each chapter offers a combination of descriptive information and problem-oriented analysis, presenting key topical issues in Germany which are relevant to an international readership. Sabine Kuhlmann is Professor of Political Science, Public Administration and Organization at Potsdam University, Germany, Vice President of the IIAS for Western Europe, and Vice-Chair of the National Regulatory Control Council of the German Federal Government. Isabella Proeller is Professor for Public and Nonprofit Management at the University of Potsdam, Germany. Dieter Schimanke is former Professor of Public Administration at the Helmut-Schmidt-University in Hamburg, Germany. He became Secretary of State in a state in East Germany after unification and since his retirement, he is Senior Expert in projects of GIZ on reforms of Public Administration (mainly in Eastern Europe and Asia). Jan Ziekow is Professor of Public Law and the Director of the German Research Institute for Public Administration, Germany, Vice-President and former President of the German Section of IIAS.